Lydia's charm - Brunstetter, Wanda E. (Uhrichsville, OH : Barbour Pub., 2010)
When Lydia King suddenly finds herself widowed and jobless, she moves to Charm, Ohio, to be close to her mother and help with her grandfather. But when tragedy strikes her young life yet again, can she find strength in a family of young boys who need a mother, or will the gifts from a secret admirer prompt her to pursue an impossible love?
"An Amish widow starts over in Charm, Ohio"--Cover.
Includes discussion questions.
Keywords: Amish -- Ohio -- Fiction; Widows -- Fiction; Single mothers -- Fiction; Ohio -- Fiction; Christian fiction; Love stories